De un tipo textual memoria: ¿primer documento judicial mestizo en el Perú del siglo XVI? - Huamanchumo de la Cuba, Ofelia (2011)
This paper addresses the constituent features of the textual type calledmemoria, in the context of the legal-administrative sphere of the ColonialEra. This textual type is embedded in both the Spanish and the native American legal tradition, so it is of particular interest for the history ofthe Spanish language, for the textual linguistics studies and for pragmaticsstudies. The research also aims to demonstrate that in the Peruvian judicial system of the 16th Century there was a particular type of memoria, modeledby the convergence of the Western way of recording data and the useof quipus as Andean recording medium.